The Salford Gait Tool: Does the clinical experience of the raters influence the inter-rater reliability?. (17th February 2018) - Paci, Matteo; Mini, Giuditta; Marchettini, Mariangela; Ferrarello, Francesco
ABSTRACT: Purpose : The purpose of this study was to verify if the amount of experience or the specific professional field of the raters may influence inter-rater reliability of the Salford Gait Tool (SF-GT). Methods : Standardized videos of gait of seven children with cerebral palsy were recorded and assessed by three physiotherapists with experience in pediatrics (PPTs), three physiotherapists with experience with adult individuals (n-PPTs), and three students of physiotherapy. Results : The inter-rater reliability both for joints and gait events was acceptable (ICC ≥ .70) for PPTs and n-PPTs, but not for students. Conclusions : The inter-rater reliability of the SF-GT can be influenced by the experience of the raters and the amount of clinical experience seems to be more relevant than the specific professional field. Further research should be conducted with larger samples.